Processing of Clinker Incinerator Dust - Yu. Kh. Khidirova (International Journal on Orange Technologies, 2021)
Physical and chemical substantiation and development of effective technologies for processing dust klinkeroobzhigatelnyh furnaces to produce liquid and granular nitrogen-calcium fertilizer with the establishment of optimal production parameters.